Redefining the in-place economy and women’s role in the local economy of highland areas - Magali Talandier (Revue de Géographie Alpine)
The in-place, or presential, economy has become the prime source of jobs in France’s highland areas. Yet little research has investigated this category of activity, which is also undervalued by economic players. Focusing primarily on production, classical economic analysis has minimized both the economic and social role of these sectors, and by extension the part played by women in local economies. In the highland areas of France two-thirds of in-place jobs are held by women. We shall see from France’s six mountain ranges that such jobs are vital for sustaining local economies and the living standards of households. Apart from providing a second income, these jobs, which are less under threat than those in which men are predominant, act as a powerful shock-absorber against the fluctuations of the global economy.in-place economy, residential economy, rural development, highlands, gender